2018
DOI: 10.1002/slct.201702801
|View full text |Cite
|
Sign up to set email alerts
|

Co(II) or Cu(II) Schiff Base Complex Immobilized onto Carbon Nanotubes as a Synergistic Catalyst for the Oxygen Reduction Reaction

Abstract: Heterogenization of molecular catalysts not only showed excellent activity and selectivity in many catalytic reactions, but also provided definite active sites feasible to explore the reaction mechanism. Herein, we report a heterogenization of metal Schiff‐base complex immobilized on multiwalled carbon nanotubes (MWCNTs) as a high‐performance catalyst for the oxygen reduction reaction (ORR). Although MWCNTs alone have little catalytic activity, the heterogenization hybrid exhibits an enhanced ORR activity in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This indicates that the coordination of Co 2+ and Ni 2+ metal ions to –NH 2 group could not change the oxidation states due to less coordination tendency of –NH 2 group. However, the Cu‐MOF exhibits the peaks for both Cu 2+ (955.34 and 935.06 eV) and Cu + (952.82 and 933.01 eV) oxidation states . The existence of both +2 and +1 states can be ascribed to: i) the effective coordination of –NH 2 group through non‐bonded electrons of nitrogen and ii) the formation oxide layer on Ti‐MOF surface, which further confirms the existence of CuO x after the coordination as supported by XRD analysis.…”
Section: Resultssupporting
confidence: 58%
“…This indicates that the coordination of Co 2+ and Ni 2+ metal ions to –NH 2 group could not change the oxidation states due to less coordination tendency of –NH 2 group. However, the Cu‐MOF exhibits the peaks for both Cu 2+ (955.34 and 935.06 eV) and Cu + (952.82 and 933.01 eV) oxidation states . The existence of both +2 and +1 states can be ascribed to: i) the effective coordination of –NH 2 group through non‐bonded electrons of nitrogen and ii) the formation oxide layer on Ti‐MOF surface, which further confirms the existence of CuO x after the coordination as supported by XRD analysis.…”
Section: Resultssupporting
confidence: 58%
“…The rich voids, open pore structure, and large surface area of Zn-MOF-74 can benefit to the plentiful deposition of Pt, Cu nanoparticles onto the carbon, leading to a favorable surface area prepared doped materials in this study like Cu x /Zn-MOF-74 and Pt/Cu/Zn-MOF-74. The distribution of pores may benefit from the exposure of more abundant catalytic active sites and improved mass transfer during the electrochemical reactions [60][61][62]. At the carbonization temperature of 900 °C, the slight decrease in specific surface area and pore volume can be attributed to the rapid evaporation of zinc and agglomeration of nanoparticles.…”
Section: Specific Surface Area Characterizationmentioning
confidence: 99%
“…When the surface Cu was functionalized with O atoms, it exhibited enhanced ORR activity, which can be compared with the Pt(111) surface [60]. Bai et al found that the ORR activity can be enhanced by the combined effect of copper and nitrogen in a copper oxide/nitrogen-doped reduced graphene oxide catalyst [61]. Chen et al reported a ZIF-8 framework derived Cu−N/C electrocatalyst with N−Cu II −Cu 0 sites showing efficient ORR electrocatalysis [62].…”
Section: Introductionmentioning
confidence: 99%
“…16−19 In addition, supported Cu-based complexes exhibited ORR activity in alkaline electrolyte. 20,21 The electron configuration of Cu can be adjusted by the ligands, which in turn influences the catalytic performance. 22,23 Han et al carried out DFT calculations to identify the ORR mechanisms over copper-supported N-doped graphene.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are seldom reported in reduction reactions, especially ORR. Cu-based nanoparticles embedded in carbon materials are active in electrocatalytic ORR. In addition, supported Cu-based complexes exhibited ORR activity in alkaline electrolyte. , The electron configuration of Cu can be adjusted by the ligands, which in turn influences the catalytic performance. , Han et al carried out DFT calculations to identify the ORR mechanisms over copper-supported N-doped graphene . When the surface Cu was functionalized with O atoms, it exhibited enhanced ORR activity, which can be compared with the Pt(111) surface .…”
Section: Introductionmentioning
confidence: 99%